Experimental Investigation of Forced Convection Heat Transfer Enhancement in Dimpled Tube - Vilas P. Apet; Sachin L. Borse (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
The development of high-performance thermal systems has stimulated interest in methods to improve heat transfer. Tubes with artificial roughness obtained by providing dimples on the tube surface are competitive in comparison to performance and cost of other enhanced techniques currently employed in turbulent flow. In this study forced convection heat transfer characteristics from dimpled tube has been investigated experimentally. The effect of variation in dimple diameter and dimple arrangement (inline and staggered) has been investigated for Reynolds No range 12000 to 26000 dimpled tube. Additionally the effect of variation in dimple tube and diameter on pressure drop across test section has also been investigated. This investigation was carried out to observe if the use of dimples on tube can enhance heat transfer characteristics without severe penalties associated with pressure drops for turbulent flow. The results show that heat transfer enhancement under forced convection can be achieved by using dimple tubes. The enhancement in convective heat transfer coefficient is observed as 18% and in Nusselt number as 22 % as compared with plain tube for same Reynolds number. The thermal performance factor values for the staggered dimpled array geometry were more than corresponding inline dimpled array geometry in the Reynolds number range studied .